If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(9p+2)=0
We simplify the equation to the form, which is simple to understand
4(9p+2)=0
Reorder the terms in parentheses
+(+36p+8)=0
Remove unnecessary parentheses
+36p+8=0
We move all terms containing p to the left and all other terms to the right.
+36p=0-8
We simplify left and right side of the equation.
+36p=-8
We divide both sides of the equation by 36 to get p.
p=-0.222222222222
| (4+u)(4u-3)=0 | | 126-5x=22x+21 | | 36x^2+8x-13=0 | | 2(7-x)+2(19-3x)=x | | t-3t=8 | | -45=15y | | 2.2v+1.8=-4.6v-5 | | -6s=90 | | -3x-(-4-2x)=2x+3 | | -6z-6=6(-z+2) | | x^2-8x-29=(x+a)(x+a)+b | | 7-k=1 | | -(2+w)=2 | | 7x-(8x+2)=2x-50 | | |6X-8|=2 | | 7y+2y=3 | | -1-5(-8z-1)=-6(-6z+5)+3 | | 5=5(-21)+4 | | 19-10j=-11 | | 20-3x/8+5x+4/12=3 | | 3=5(-19)+4 | | 8y^2+24y-80=0 | | 14/11= | | -2.3-4.2r=-37.58 | | 4x^2-42x+45=0 | | 5=-5(-29)+4 | | 6(z-7)=3 | | -8x+14=-2[4x-7] | | 7z=-35 | | -0.75(z+0.17)=0.2(z-0.375) | | 8a-9a=7a-6 | | 2x-3x=-4 |